MAINTENANCE ON SUGAR CANE MILL ROLLERS TO PREVENT WEAR AND DAMAGE - Harsa Dhani; Jahu, Reinardi Oddilian; Redationo, Nereus Tugur (Universitas Katolik Widya Karya Malang, 2023)
One of the reasons the Sugar Factory failed to meet its sugar production target was due to damage to the machine components, particularly at the milling station, where the milling rollers are located. The milling rollers play a crucial role in extracting juice from sugar cane, separating the juice from the bagasse, and measuring the raw juice before it enters the purification process. This unit is designed to maximize raw juice yield while minimizing the amount of bagasse. The milling rollers are arranged in a triangular configuration of three mills, with a milling path between the front and rear rollers that can move forward and backward. Several common issues affect the milling rollers, including surface wear, damage from excessive loads, and wear from repeated friction between the rollers and the sugar cane. Sugar cane itself contributes to roller wear due to its composition, which includes water, sucrose, cellulose, lignin, hemicellulose, ash, and silica. These substances are highly corrosive, even to stainless steel, and act like abrasives against the rollers. The usual remedy at the factory is to weld stainless steel onto cast iron rollers. However, this method has only been moderately effective, as the rollers continue to experience wear after a short period. Based on field observations and literature reviews, some suggested solutions include more frequent cleaning and applying a tungsten coating to the roller surfaces.